М.М. Бабич – талантливый ученый, конструктор и организатор производства - Бондаренко, В.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The paper shows the main scientific resects, design developments and achieve-ments in the setting up of hard alloy production attained by M. M. Babich, a specialist in the hard alloy technology, well-known in the USSR, Germany and Ukraine.